Analysis of The Value of Character Education in The Novel Dikta Dan Hukum By Dhia'an Farah and it’s Implementation in Indonesian Language Learning - Khusna, Nela; Masrurih, M.; Fajri, Khoirul (Golden Ratio of Social Science and Education, 2025)
The main purpose of this study is to conduct an in-depth analysis of the value of character education contained in the novel Dikta dan Hukum by Dhia'an Farah. The focus of this research also involves the implementation of these values in the Indonesian learning process in grade XI of SMK. The method used is a descriptive method with a qualitative data analysis approach, and research instruments in the form of non-test instruments. The data collection techniques applied in this study cover various aspects, such as observation, reading, listening, understanding, and note-taking. Through the results of the research, it was concluded that there were 21 data on Character Education Values which included 5 religious values, 4 hard work values, 4 honest values, 5 social care values, and 3 friendly/communicative values in the novel Dikta and Law which became the focus of the analysis. The results of this study can be used as an important contribution to further understanding related to the implementation of character education values in the context of Indonesian language learning at the vocational school level. An in-depth analysis of the character values that appear in literary works can be the basis for the development of curriculum and teaching methods that are more relevant to the needs of students' character education. Thus, this research has the potential to make a positive contribution to the development of character education in Vocational High Schools.